1984
DOI: 10.1039/dt9840000125
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of rhodium(I) with 1,8-naphthyridine and related ligands. Crystal structure of [Rh2(µ-napy)2(nbd)2][ClO4]2·H2O

Abstract: Nord-Orientale, Bologna, with financial support f r o m the University of P a r m a .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

1984
1984
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 14 publications
0
11
1
Order By: Relevance
“…However the FAB+ mass spectrum shows a peak corresponding to the cation [Pt(C 6 F 5 ) 2 (napy)] + suggesting a mononuclear formula for this complex. This was not the expected result, since the napy or napylike ligands have frequently been used as dinucleating bridging ligands to force the proximity of the metal centers [22][23][24][25][26][27][28][29][30] and only in a few cases do these ligands behave as chelating. [31][32][33][34][35] The formation of a very strained four-membered ring in the chelate is in all likelihood the reason for the small number of complexes of this type.…”
Section: Synthesis and Characterization Of [Pt(c 6 F 5 ) 2 (Napy)] (1)mentioning
confidence: 99%
“…However the FAB+ mass spectrum shows a peak corresponding to the cation [Pt(C 6 F 5 ) 2 (napy)] + suggesting a mononuclear formula for this complex. This was not the expected result, since the napy or napylike ligands have frequently been used as dinucleating bridging ligands to force the proximity of the metal centers [22][23][24][25][26][27][28][29][30] and only in a few cases do these ligands behave as chelating. [31][32][33][34][35] The formation of a very strained four-membered ring in the chelate is in all likelihood the reason for the small number of complexes of this type.…”
Section: Synthesis and Characterization Of [Pt(c 6 F 5 ) 2 (Napy)] (1)mentioning
confidence: 99%
“…Indeed one the few examples of thoroughly studied mechanisms of Ru complexes with nitrogencontaining ligands have been reported by Frediani et al [21] The hydroformilation activities for 1-hexene reported in this work are in the range of 8-33%, with a high selectivity towards the lineal product. RuCl 3 hydrated and Ru 3 (CO) 12 have been used as catalysts in the hydroformilation of olefin with nonattractive activities. [22] The activities for the hydroformilation reported by us in this work are similar to those reported for 1-hexene [21] and propene [23] (with conversions in the range of 30-50%).…”
Section: Hydroformylation Of Styrenementioning
confidence: 99%
“…for similar complexes (Tiripicchio, Camellini, Uson, Oro, Ciriano & Viguri, 1984;Oro, Ciriano, Villarroya, Tiripicchio & Lahoz, 1984;Lahoz, Tiripicchio, Camellini, Oro & Pinillos, 1985). The central five-membered ring of ligand (1) The bite angle N-Rh-N ofligand (1) in the complex is 81.9 (2) ° with the lone pairs pointing almost directly toward the Rh t ion [C(5)-N-Rh = 175.1 (2)°1.…”
Section: > mentioning
confidence: 99%
“…Recently, the heptacyclic ligand (1), a bis(2,3-quinolino) derivative of cis,syn,cis-tricyclo-© 1989 International Union of Crystallography 16.3.0.03.71undecane, was prepared as indicated in the scheme ) and the crystal structure was determined (Marchand, Annapurna, Flippen-Anderson, Gilardi & George, 1988). Many potentially binucleating ligands such as 1,8-naphthyridine (Tiripicchio, Camellini, Uson, Oro, Ciriano & Viguri, 1984), 7-azaindole (Oro, Ciriano, Villarroya, Tiripicchio & Lahoz, 1984) and pyrazole and its derivatives (Uson, Oro, Ciriano, Carmona, Tiripicchio & Camellini, 1982) form complexes in which the ligand bridges binuclear Rh 2 units. In the case of amidinato complexes of Rh I with cod (1,5-cyclooctadiene), tfbb (tetrafluorobenzo15,61bicyclo12.2.21-octa-2,5,7-triene) and nbd (norbornadiene) both mononuclear and binuclear Rh t complexes can be prepared depending upon the nature of the two ligands and upon the resulting steric interactions (Lahoz, Tiripicchio, Camellini, Oro & Pinillos, 1985).…”
mentioning
confidence: 99%